DETERMINANTS OF PADDY FIELD CONVERSION IN ROTE NDAO REGENCY - Mooy, Injela Wahyuni Ayahnya; Abdurrahman, Mustafa; Darlen, Maria Fransisca (Undana Press, 2025)
Paddy field conversion is a critical issue in agricultural development because it directly reduces the availability of land for food production. Rote Ndao Regency, one of the regions with the largest paddy field areas in East Nusa Tenggara Province, has experienced a significant decline in paddy field area during the last five years. A considerable proportion of these fields has been converted into housing, small businesses, and public facilities. If the conversion of paddy fields to non-agricultural functions is not controlled, the area available for food production will continue to decrease. This study used a quantitative approach and was conducted in Rote Ndao Regency using primary and secondary data. The data were analyzed using multiple linear regression with SPSS to determine the influence of several independent variables on paddy field conversion. The results show that 3,442 hectares of paddy fields in Rote Ndao Regency have been converted. These lands are no longer used for rice farming but have been shifted to other uses, including private houses, kiosks, workshops, restaurants, and rental houses. The multiple linear regression results indicate that population growth, growth of household-scale industries, household income, paddy field location, and paddy field productivity significantly affect paddy field conversion. To support food security programs, the government should tighten the permit system for converting agricultural land into non-agricultural land, strengthen the designation of sustainable food agricultural land, and provide extension services that encourage farmers to use existing agricultural land more productively and sustainably.